A family-centered pediatric outpatient clinic for children ages 6-12 years old - Alegria, Maria Carla C.; Mayo, Adelaida Villaraza (2005.)
Using the family-centered care approach in healthcare design, this study focused on proposing design solutions for a pediatric outpatient clinic which addressed the needs of children ages six to twelve years old as well as their families who accompany them to the clinic. The data were gathered through interviews, questionnaires, and observations of an actual pediatric outpatient clinic were analyzed using several design factors in planning a good design for a pediatric clinic. Based on the children's responses to the interviews, results showed that children prefer more a pediatric outpatient clinic that is welcoming, comfortable and home-like; a place where they can explore and experience interesting things like toys and books. Similarly, the parents' responses indicated that the clinic, to cater to their needs and their children's needs as well, must be home-like with facilities/materials that can stimulate the motor and cognitive development of their children. The study concludes that the best setting for a pediatric clinic to be a unified environment that addresses the needs of its patients is for it to be home-like and capable of stimulating a child's developmental growth. In proposing effective design solutions for pediatric outpatient clinics, basic design standards are not enough bases in coming up with an effective design for a pediatric clinic. It is important to consider the needs, preferences and choices of its users, the patients and the family who accompany them to the clinic.
Thesis(BID)--University of the Philippines Diliman.
Title from cover.
Keywords: Pediatric clinics; Interior decoration